SysML for systems engineering - Holt, Jon; Perry, Simon (Institution of Engineering and Technology, 2008)
The book reviews developments in the following fields: introduction to systems engineering; modelling requirements; SysML diagrams; physical systems; interfaces and constraints; process modelling with SysML; and using SysML concepts in UML.